NEP 2020: IMPACTS ON INDIAN EDUCATION SYSTEM AND STAKEHOLDERS - Gowher Hassan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Education wields significant influence in nation-building, shaping the destiny of both the nation and its people. Its enduring effects are pivotal for a country's growth and progress, underscoring its indispensable role in the contemporary context. A stark contrast in growth and development is evident when comparing the eras before and after independence. Presently, the Indian Government is set to overhaul our education system after a 34-year interval, marking the third amendment to the education policy. The National Education Policy 2020 introduces numerous proposed changes that will inevitably impact all stakeholders. This study aims to delve into the National Education Policy 2020, scrutinizing its repercussions on stakeholders. Furthermore, the paper seeks to raise awareness regarding the policy's impending influence and future implications by eliciting a series of inquiries distributed across various social media platforms and subsequently analyzing the responses received.